Evaluation and Bioinduction of Energy Components in Jatropha curcas L. - Augustus, G.D.P.S.; Mehalingam, P.; Kannan, D.; Kumari, G.D.S.; Jayabalan, M. (Asian Journal of Chemistry, 2016)
Jatropha curcas L. is a multipurpose species with many attributes and considerable potential. The oil from the seeds is potentially the most valuable end product. Nearly 40% of the land area in India is wasteland. However, a large number of latex bearing and oil yielding plants can grow under such unfavourable agro-climatic conditions. J. curcas, a Euphorbiaceae, grows well under such adverse climatic conditions because of its low moisture demands, fertility requirements, and tolerance to high temperatures. The seed contains 19.0 oil, 4.7 polyphenol, and 3.9% hydrocarbon. This semi-drying oil could be an efficient substitute for diesel fuel. The gross calorific value for the seed (0% moisture content) was 4980.3 cal/g (20.85 MJ/kg), oil was 9036.1 cal/g (37.83 MJ/kg), and hydrocarbon was 9704.4 cal/g (40.63 MJ/kg). The oil fraction consists of saturated fatty acids: palmitic acid (14.1%), stearic acid (6.7%) and unsaturated fatty acids: oleic acid (47.0%), linoleic acid (31.6%). Treatment of plants with growth regulators significantly influences the production of hydrocarbons. Among the treatments, ethephon and morphactin induced the maximum production of hydrocarbon with 5.0 and 5.4%, respectively.